2018
DOI: 10.3390/hydrology5020022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Use Change on Flow and Sediment Yields in the Khokana Outlet of the Bagmati River, Kathmandu, Nepal

Abstract: Land use changes are a key factor for altering hydrological response, and understanding its impacts can help to develop a sustainable and pragmatic strategy in order to preserve a watershed. The objective of this research is to estimate the impact of land use changes on Bagmati river discharge and sediment yield at the Khokana gauging station of the Kathmandu valley outlet. This study analyzes the impact of land use changes from the year 2000 to 2010 using a semi-distributed hydrological, Soil Water Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
2
26
0
1
Order By: Relevance
“…To better analyze and reduce the uncertainty of the river runoff, a two-year warm-up period was considered. All the calibration of the model parameters was done manually and the base value of the parameters were taken from the previous studies [5,6,15,16,34]. The model performance was evaluated based on widely used statistical parameters such as Nash-Sutcliffe simulation efficiency (NSE), percentage bias (PBIAS), coefficient of determination (R 2 ), and the ratio of root mean square error (RMSE) to standard deviation ratio (RSR).…”
Section: (Ii) Model Setup Calibration and Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…To better analyze and reduce the uncertainty of the river runoff, a two-year warm-up period was considered. All the calibration of the model parameters was done manually and the base value of the parameters were taken from the previous studies [5,6,15,16,34]. The model performance was evaluated based on widely used statistical parameters such as Nash-Sutcliffe simulation efficiency (NSE), percentage bias (PBIAS), coefficient of determination (R 2 ), and the ratio of root mean square error (RMSE) to standard deviation ratio (RSR).…”
Section: (Ii) Model Setup Calibration and Validationmentioning
confidence: 99%
“…The LULC change is becoming a common problem for developing countries that have economies basically dependent on agriculture [6]. Conversion of the LULC type due to urbanization has affected sustainable management of water resources [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…River discharge from the upper catchment during 1992-2017 has decreased by −2.05% per year even though the rate of rainfall decrease is only −0.83%. Despite an increase in urban area, which generally results in higher surface runoff [97,98], the MK test on 1992-2017 estimated that surface runoff for the upper catchment showed a significant decrease of −1.51%. Multiple regression analysis suggested that, compared to the influence of LULC changes, a decrease in rainfall is more influential on river discharge from the upper catchment.…”
Section: The Influences Of Rainfall and Lulc Changes On River Dischargementioning
confidence: 99%